Analysis of Productive Zakat and GDP on Poverty Levels and Governance of Zakat Institutions in West Sumatra - Herdian Mainaki; Anton Bawono; Wahyu Wibowo (MAMEN: Jurnal Manajemen, 2026)
This study investigates the effects of Gross Regional Domestic Product (GRDP/PDRB), productive zakat, and zakat governance on poverty in West Sumatra, using a Moderated Regression Analysis (MRA) approach based on panel data from 19 districts/cities for the period 2020–2024. The findings reveal that PDRB has a significant negative effect on poverty, indicating that higher regional economic output contributes to lower poverty rates. A 1% increase in PDRB reduces poverty by –5.59E-05%, consistent with economic growth trends and declining poverty levels in West Sumatra in recent years. Conversely, productive zakat shows a negative but statistically insignificant effect on poverty, suggesting that its contribution remains limited at the provincial scale due to the relatively small allocation of productive zakat compared to consumptive distribution. The study also documents that zakat governance significantly strengthens the impact of PDRB on poverty reduction, but does not moderate the effect of productive zakat on poverty. These results emphasize the importance of improving zakat management, increasing productive distribution ratios, and strengthening empowerment-based programs to enhance zakat’s role in poverty alleviation. Future research is recommended to incorporate mediating variables such as employment and investment, and apply causal analysis methods to deepen the understanding of zakat’s economic impact.